(untitled) (International relations and international law Journal, 2018)
China and Japan are the most important powers in Asia-Pacific region now. China, Japan and other Asia-Pacific countries are facing with strategically importants cases, such as to keep region in the world and to maintain its economic vitality in globalized system conditions. The stability in East Asia depends on a strong and predictable relations between China and Japan. And one of the main aspects is to look through the history of the relations. Article considered such themes as Status of Taiwan, Sino-Japanese Peace and Friendship Treaty, Yasukuni Shrine issue, significance of East China sea agreement, political, economic and military and relations. Key words: Asia-Pacific, China-Japan, Taiwan, Yasukuni Shrine, East China sea, balance of power.